Cu-Mn-Co-P alloy and manufacturing method thereof
Through the preparation of Cu-Mn-Co-P-based copper alloy materials, combined with the component ratio and process processing of Mn, Co, and P, the shortcomings of existing copper alloy materials in high strength and high conductivity and bending processability are solved, and the problem of the bending processability of the existing copper alloy materials is achieved. The balance of conductivity and tensile strength and bending processability meet the needs of high transmission and miniaturization of high-speed railways and electronic components.
Patent Information
- Application Number
- CN202410884330.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-03
- Publication Date
- 2024-12-27
AI Technical Summary
In terms of conductivity, strength and bending processability, existing copper alloy materials are difficult to achieve the comprehensive characteristics of high-strength high-conductivity factor σ exceeding 450, and cannot meet the demands of high-speed railways, electric vehicles and electronic components for high transmission, miniaturization and density. .
By studying the characteristics of Cu-Mn-P and Cu-Co-P alloys, combining the component ratio and relationship of Mn, Co, and P, a special structure is formed, and continuous or semi-continuous casting, hot processing, cold processing, solid dissolution is used to form a special structure. Through the process of aging, Cu-Mn-Co-P-based copper alloy material with excellent conductivity, strength and bending processability was prepared.
The balance of conductivity and tensile strength is achieved, the high-strength high-conductivity factor σ exceeds 450, and has good bending machining properties, meeting the high transmission, miniaturization and intensive needs of high-speed railways, electric vehicles and electronic components.
Smart Images

Figure CN119194156A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a copper alloy material and a manufacturing method thereof, which is used as various connectors, integrated circuit lead frames, contact wires for high-speed railways, electric vehicles and electric switches, radiators, relays, switches and other electrical and electronic components, and which has high requirements for material conductivity and heat transfer. The copper alloy material has excellent conductivity and heat transfer, as well as good strength and bending processability. Background Art
[0002] In order to suppress the heat generated when electricity is turned on, the copper material used as the basis of various electrical and electronic components is required to have good electrical conductivity and heat transfer (heat dissipation). At the same time, in order to ensure the flow of current, there needs to be sufficient contact pressure between components, so the copper alloy material is required to have sufficiently high strength. In addition, electronic components are generally formed by bending, so the material is required to have good bending processability.
[0003] At present, the widely used high-conductivity and high-strength copper alloy materials are made of copper alloys of different composition systems according to different uses. There are two main characteristic areas: one is the conductivity of 75-85% IACS and the tensile strength of 580-500MPa, mainly Cu-Cr-(Zr) alloys (such as C18140, C18150, C18400, C18080, etc.); the other is the conductivity of about 60-65% IACS and the tensile strength of 650-600MPa, mainly Cu-Ni-P alloys (such as C19000 and KLF170 of Kobe Steel, Japan) and Cu-Co-Si alloys (NKC4419 of Nippon Mining and Metals, Japan). In the middle area between the above two, that is, the conductivity of about 70% IACS (between 65-75% IACS), there is no commercial copper alloy on the international market.
[0004] In recent years, with the high-speed transmission (high current) and miniaturization of electrical and electronic components, as well as the popularization of electric vehicles and the growth rate of high-speed railways, the strength and conductivity of the copper alloy materials used are required to be higher and higher. Due to the well-known inverse relationship between strength and conductivity, the quantitative evaluation of high-strength and high-conductivity copper alloys requires comparing the tensile strength at a specific conductivity; or comparing the conductivity at a specific tensile strength. At present, there is a simple comparison and judgment method, that is, the product of conductivity (EC) and tensile strength (TS) is used as the high-strength and high-conductivity factor σ, that is, σ=EC×TS. Generally, the unit of tensile strength is MPa and the unit of conductivity is %IACS. So far, the σ of commercial copper alloys in the international market (excluding some special high-quality grades that do not consider bending processability, heat resistance, etc.) generally does not exceed 450. For example, the corresponding tensile strength does not exceed 750 and 530MPa when the conductivity is 60 and 85%IACS.
[0005] In view of the actual needs of the market and the fact that existing copper alloys cannot meet the requirements of high strength and high conductivity factor σ exceeding 450 and good bending workability, the present invention has been developed and completed. Summary of the invention
[0006] The inventor of the present invention has conducted a detailed investigation and research on Cu-Mn-P alloy, Cu-Co-P alloy and Cu-Mn-Co-P alloy, which is a mixed component of these two alloys, based on the fact that they are different from the existing Cu-Cr alloy, Cu-Ni-P alloy and Cu-Co-Si alloy. It is found that Cu-Mn-P alloy has the same precipitation strengthening effect as Cu-Ni-P, and its precipitates are needle-shaped, which has the advantage of not being easy to coarse during aging and heat-resistant treatment (over-aging and low heat resistance). However, the disadvantage is that the electrical conductivity is 40-50% IACS, which is less than 60-65% IACS of Cu-Ni-P alloy, so Cu-Mn-P alloy has not been developed for practical use so far.
[0007] Cu-Co-P alloys have the same electrical conductivity as Cu-Cr(-Zr) alloys (80-85% IACS), and are relatively easy to manufacture (low oxidizability of elements and low solid solution temperature during dissolution casting), and have been commercialized, such as DK-10 alloy of DOWA Company of Japan and HRSC alloy of Mitsubishi Shindoh Company. However, since Cu-Co-P alloys are slightly lower in strength than Cu-Cr(-Zr) alloys (tensile strength is 30MPa lower, or hardness is about HV10 lower), they have not been further commercialized.
[0008] The inventor of the present invention has carried out research and development of Cu-Mn-Co-P alloy based on the characteristics of Cu-Mn-P alloy and Cu-Co-P alloy. It is found that under the specific composition range and mutual proportion relationship of Mn, Co, and P, as well as the specific manufacturing process conditions, Mn-P and Co-P precipitates can eventually form a special structure, achieve the superposition strengthening effect of these two precipitations, and achieve a copper alloy material with excellent comprehensive characteristics such as conductivity, strength, heat resistance and bending processability. The present invention is completed based on these findings.
[0009] Specific instructions:
[0010] One of the purposes of the present invention is to solve the deficiencies of the prior art and to provide a copper alloy material having excellent comprehensive properties such as electrical conductivity, strength, heat resistance and bending workability.
[0011] The second object of the present invention is to provide a specific manufacturing process condition for the aforementioned copper alloy material, which can ultimately achieve the formation of a special structure of Mn-P and Co-P precipitates, thereby achieving the superimposed strengthening effect of the two precipitations.
[0012] The technical solution adopted by the present invention to solve the technical problem is as follows:
[0013] The present invention provides a copper alloy material, which contains 0.10-0.60wt% Mn, 0.15-0.50wt% Co, 0.04-0.39wt% P, and the rest is Cu and inevitable impurities. The copper alloy material has the following formulas (1) and
[0014] (2) The ratio of ingredients
[0015] 0.25≤{Mn} / {Co}≤4.0……(1);
[0016] 2.8≤({Mn}+{Co}) / {P}≤5.0......(2);
[0017] Wherein {Mn}, {Co} and {P} represent the weight percentages (wt%) of Mn, Co and P in the copper alloy material, respectively.
[0018] Preferably, it contains 0.15-0.40wt% Mn, 0.15-0.35wt% Co, 0.06-0.23wt% P, and the rest is Cu and inevitable impurities. The copper alloy material has a composition ratio that satisfies the following formulas (1) and (2):
[0019] 0.5≤{Mn} / {Co}≤2.0……(1);
[0020] 3.0<({Mn}+{Co}) / {P}<4.5......(2).
[0021] Preferably, it also contains one or more selected from Ni, Fe, Mg, Cr, Sn, Zn, Zr, Ag, Ti and lanthanide rare earth elements, and the total amount thereof is less than 0.2wt%.
[0022] More preferably, it also contains one to three selected from Ni, Fe, Mg, Cr, Sn, Zn, Zr, Ag, Ti and lanthanide rare earth elements, and the total amount is 0.075-0.15wt%.
[0023] The electrical conductivity (EC) and tensile strength (TS) of the copper alloy material mentioned above satisfy the following formula (3);
[0024] {EC}×{TS}≧450……(3);
[0025] Wherein {EC} represents the electrical conductivity of the copper alloy material in %IACS, and {TS} represents the tensile strength of the copper alloy material in MPa.
[0026] Preferably, the copper alloy plate material has good bending workability with a minimum bending radius to plate thickness ratio R / t being less than 2.0.
[0027] The electrical conductivity is measured according to the method specified in JIS-H0505. The tensile strength is measured by cutting a sample from the length direction of the material according to the method specified in JIS-Z2241. The bending workability is evaluated by the ratio of the minimum bending radius R without cracking to the plate thickness t, obtained by bending the samples (all 10 mm wide) in the length direction of the plate and strip according to the 90° W-type bending method specified in JIS-H3110 in the rolling direction (LD) and the perpendicular rolling direction (TD).
[0028] The present invention provides a method for manufacturing the copper alloy material, which comprises sequentially performing the following steps on the copper alloy having the above composition: continuous or semi-continuous casting of billets, hot working such as hot rolling (hot forging, hot extrusion), cold working such as cold rolling (cold forging, cold drawing), heat treatment such as solid solution and aging, milling and pickling, and other conventional manufacturing processes. In the above manufacturing process, the specific processing heat treatment process adopts the special process conditions of the present invention.
[0029] Specifically, it includes the following steps performed in sequence:
[0030] S1: Ingot cast by continuous or semi-continuous casting, hot processed by hot rolling, hot forging or hot extrusion;
[0031] S2: Cold working by cold rolling, cold forging or cold drawing;
[0032] S3: intermediate heat treatment at 600-700°C for 30 seconds to 3 minutes;
[0033] S4: Aging treatment at 350-450℃ for 3-10 hours;
[0034] S5: Low temperature annealing after cold rolling and final cold rolling.
[0035] Preferably, the temperature of the hot working in S1 is 950-1000°C.
[0036] Preferably, in said S3, an intermediate heat treatment is performed at a temperature between 650 and 720° C. for 1 to 1.5 minutes; and in said S3, an aging treatment is performed at a temperature between 380 and 420° C. for 3 to 6 hours.
[0037] Preferably, the processing rate of the final cold rolling is 20-60%.
[0038] The copper alloy material obtained according to the present invention has excellent comprehensive properties that are difficult to obtain with the existing alloy composition and manufacturing technology. It is produced to meet the foreseeable future needs for high current high transmission, miniaturization and density of electronic components. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 a: Comparative Example No. 15 (84% IACS, HV146) with a relatively high Co content, spherical precipitates;
[0040] Figure 1 Middle b: Comparative Example No. 16 (56.2% IACS, HV173) with a relatively high Mn content, needle-shaped precipitates;
[0041] Figure 1 Middle c: Comparative Example No. 22 (64.1% IACS, HV168) of conventional process (without intermediate heat treatment), needle-shaped and spherical precipitates are mixed;
[0042] Figure 1 Middle d: Inventive Example No. 2 (72.4% IACS, HV192), a special precipitate with a needle shape contained inside a spherical shape.
[0043] Specific implementation method description
[0044] 1. Alloy composition
[0045] Mn (manganese) and Co (cobalt) can both form compounds with P (phosphorus), and the precipitation strengthening of these compounds can be used to improve the strength of copper alloys. When the Mn content is less than 0.1wt%, the precipitation strengthening effect is insufficient; if the Mn content exceeds 0.6wt%, it is easy to cause excessively low conductivity, and it is difficult to achieve the final conductivity of the material exceeding 60% IACS. When the Co content is less than 0.15wt%, the precipitation strengthening effect is insufficient; if it exceeds 0.5wt%, the required high solid solution temperature makes industrial production difficult, and Co is a relatively high-priced element that is not conducive to material costs. That is, the Mn content is between 0.1-0.6wt%, and the Co content is between 0.15-0.5wt%. Preferably, the Mn content is between 0.15-0.4wt%, and the Co content is between 0.15-0.35wt%.
[0046] The purpose of the present invention is to make full use of the superposition effect of precipitation strengthening of Mn-P and Co-P compounds, so the content of Mn and Co cannot differ too much and should satisfy the following formula (1):
[0047] 0.25≤{Mn} / {Co}≤4.0……(1);
[0048] Another way to express it is that {Mn} or {Co} accounts for more than 20% but less than 80% of {Mn+Co}. If the {Mn} / {Co} ratio is less than 0.25 or greater than 4.0, the content of Mn and Co differs too much, and the resulting alloy properties are close to Cu-Mn-P alloy or Cu-Co-P alloy, which cannot achieve the purpose of the present invention. A more suitable {Mn} / {Co} ratio is greater than 0.5 and less than 2.0.
[0049] P (phosphorus) can form precipitates with Mn and Co to achieve precipitation strengthening. There are many types of precipitates, which vary with the content ratio of P, Mn and Co. The results of the present invention found that the balance between conductivity and strength is best when the content ratio of Mn, Co and P is within the range of the following formula (2).
[0050] 2.8≤({Mn}+{Co}) / {P}≤5.0……(2)
[0051] This ratio reflects the balance of the contents of Mn, Co and P compounds. Less than 2.8 or greater than 5.0 indicates an excess or deficiency of P content, which will lead to low conductivity and strength. The preferred ratio of {Mn}+{Co}) / {P} is between 3.0 and 4.5. According to the Mn and Co content range and formula (2), the P content is between 0.04-0.39wt%. In addition, if the P content is too high (for example, more than 0.3wt%), hot working cracking problems are likely to occur. Therefore, within the range that satisfies formula (2), from the perspective of manufacturability, the upper limit of the ratio in formula (2), that is, a lower value of P content, is selected as much as possible. The preferred P content is between 0.06-0.23wt%.
[0052] For other elements, if necessary, one or more elements selected from Ni, Fe, Mg, Cr, Sn, Zn, Zr, Ag, Ti and lanthanide rare earth elements may be further contained according to specific circumstances. For example, Cr, Fe, Mg, Zr, Ti and lanthanide rare earth elements have the effect of refining grains and improving heat resistance; Sn and Ni have a solid solution strengthening effect; Zn has the effect of preventing the surface electroplating layer from falling off, and Ag has the effect of improving conductivity, etc. When one or more of these elements are added, the various effects mentioned above should be fully exerted, and the total content is preferably above 0.01wt%. However, excessive content of the above-mentioned various elements can easily lead to a decrease in conductivity and destroy the balance relationship between Mn-Co-P, resulting in low characteristics. Therefore, the total content of these elements is preferably controlled below 0.15wt%, more preferably below 0.1wt%, such as 0.075%.
[0053] 2. Characteristics
[0054] 1. Electrical conductivity (and thermal conductivity) and strength:
[0055] At present, the most commonly used high-conductivity and high-strength copper alloy strips for high-speed railway contact lines, smart phones, computers and other components (power terminals, USB, chargers, etc.) can be divided into two categories: one is the Cu-Cr(-Zr) alloy and Cu-Co-P alloy with a conductivity of about 80% IACS (75-85% IACS), and a tensile strength of 570-500MPa; the other is the Cu-Ni-P and Cu-Co-Si alloys with a conductivity of 60-65% IACS, and a tensile strength of 650-600MPa. The high-strength and high-conductivity factor σ is difficult to break through 450.
[0056] With the miniaturization of electrical and electronic components, the strength requirements for copper alloy materials are increasing, and the strength of the former type of copper alloys cannot meet the requirements; on the other hand, with the development requirements of large current, high-speed transmission and fast charging, not only the conductivity but also the strength of the latter type of copper alloys cannot meet the requirements; between the two types, for copper alloys with good property balance, the conductivity is around 70% IACS and the tensile strength reaches σ≧450 (i.e., conductivity ≧70% IACS, tensile strength ≧650MPa) copper alloy materials are still blank, and the market requirements are getting higher and higher.
[0057] The temperature rise problem caused by high-speed transmission of large current is becoming more and more serious, and copper alloy materials are required to have better heat dissipation (thermal conductivity). Since the thermal conductivity coefficient is directly proportional to the electrical conductivity, heat dissipation and electrical conductivity are generally unified, that is, the good or bad electrical conductivity can be uniformly expressed.
[0058] Bending workability: For high-conductivity copper alloy applications, relatively low bending workability is generally required. If the directions on the plate surface that are parallel and perpendicular to the rolling direction are called LD and TD directions respectively, the bending workability in the LD and TD directions is required to meet the requirement that the ratio R / t of the minimum bending radius R and plate thickness t that does not cause cracks during 90° W-type bending is generally required to be below 2.0. The bending workability in the LD direction mentioned here means that the sample is cut in a direction parallel to the rolling direction, and the bending axis during the bending process is the TD direction. Similarly, the bending workability in the TD direction means that the sample is cut in a direction perpendicular to the rolling direction, and the bending axis during the bending process is the LD direction.
[0059] 3. Manufacturing method
[0060] The copper alloy material of the present invention described above may be in the form of plates, strips, rods, wires, tubes and special-shaped materials, and may be manufactured, for example, through the following general process flow: melting / casting - heating hot working (hot rolling, hot forging, hot extrusion, etc.) - cold working (cold rolling, cold forging, drawing, etc.) - heat treatment (solid solution, aging, recrystallization annealing, etc.) - final finishing - low temperature stress relief annealing, etc.
[0061] However, as described below, the control of several process conditions is very important. In addition, although not mentioned above, optional milling (facing) can be performed after hot rolling, and optional pickling, grinding or degreasing, stretch bending and straightening can be performed after heat treatment according to actual needs. The following is a further explanation of each process using the plate and strip material with the most complex manufacturing process.
[0062] 1. [Melting casting]
[0063] The continuous and semi-continuous casting methods of general copper alloys can be used. In order to prevent P oxidation, P should be added before casting after Cu and other alloy elements are completely dissolved. Charcoal can also be added to the melting furnace and launder, and nitrogen protection can be passed.
[0064] 2. [Heating-hot processing]
[0065] The heating temperature of general copper alloys is between 900-950°C. The copper alloy of the present invention has a relatively high solid solution temperature of coarse Mn-P and Co-P compounds solidified between dendrites in the casting structure. Therefore, the heating temperature is appropriately higher than the heating temperature of general copper alloys, between 950-1000°C. If the heating temperature is not high enough, Mn-P and Co-P compounds cannot be completely dissolved (some remain), and less fine precipitation is produced during the final aging, resulting in low strength.
[0066] The ingot is heated between 950-1000℃ for 3-5 hours and then hot processed (hot rolling, hot forging, hot extrusion, etc.). The hot processing process can be carried out according to the process of general copper alloy. It is best to water cool as much as possible after hot processing to prevent the precipitation of Mn-P and Co-P compounds.
[0067] 3. [Cold working]
[0068] Next, cold working is carried out to the specified size according to the final product size and final processing rate.
[0069] 4. [Solution treatment]
[0070] In order to dissolve the small amount of Mn-P and Co-P compounds precipitated during the hot working process, a solution treatment is performed. The appropriate solution treatment temperature varies with the alloy composition. Within the alloy composition range of the present invention, the appropriate solution treatment temperature is 800-1000°C, and the treatment time can be between a few seconds and a few minutes. The appropriate solution treatment time varies with the treatment temperature and material size, and can be determined by experiments. Specifically, it can be determined by observing the structure after the solution treatment. The precise method is to observe the presence of precipitates through a transmission electron microscope, or to use a simple metallographic observation method, with a recrystallized grain diameter of about 10μm as the condition for the precipitates to be basically dissolved.
[0071] If the hot working temperature is relatively high, the cooling speed after hot working is fast, and the precipitates are small, this solution treatment can be omitted. Or if the conductivity requirement for the final product is relatively high and the strength requirement is relatively low, this solution treatment can also be omitted.
[0072] 5. [Cooling control after solution treatment]
[0073] In order to prevent precipitation and coarsening of precipitates during the cooling process after conventional solution treatment, rapid cooling (or water cooling) is required after solution comes out, which is the so-called quenching. Next, according to the general process flow, aging treatment (or cold working-aging treatment) is carried out. General precipitation-type copper alloys have an optimal precipitation temperature Tm (also aging temperature) range. When aging at a temperature higher than Tm, there are few precipitate nuclei and the precipitates grow quickly due to the high temperature, resulting in large size and low density of precipitates, and small precipitation strengthening effect; when aging at a temperature lower than Tm, the nucleation and growth of the precipitates are slow, and the precipitation strengthening effect is also small, or a very long aging time is required and large-scale production cannot be carried out.
[0074] Cu-Mn-Co-P alloys have two types of precipitates, Mn-P and Co-P, corresponding to different precipitation temperature ranges. The precipitation temperature range of Co-P precipitates is about 500-800℃, and the precipitation temperature range of Mn-P precipitates is 300-500℃. If the Cu-Mn-Co-P alloy is aged at a relatively high temperature (such as 550℃) for Co-P precipitation, the temperature is too high relative to the Mn-P precipitates, the density of the Mn-P precipitates is small and they grow rapidly, and the precipitation strengthening effect becomes very small; if it is aged at a relatively low temperature (such as 400℃), the temperature is too low relative to the Co-P precipitates, so the precipitation amount is small, and the precipitation strengthening effect becomes very small.
[0075] The present invention adopts a slow cooling treatment after the solution treatment, which is opposite to the traditional rapid cooling treatment. The purpose is to retain the material at a high temperature (such as 900-950°C) for a few seconds to tens of seconds after the solution treatment is cooled to about 600°C, so as to allow the Co-P compound to precipitate partially, and it will not coarsen due to the short time. At the same time, in this temperature range, a small amount of precipitation of Mn-P compounds will promote the refinement of Co-P precipitates. The cooling control after the solution treatment can be controlled by a conventional continuous annealing furnace (such as an air cushion furnace and a vertical furnace with multiple heating-cooling zones) by adjusting the cooling conditions (air pressure and airflow, etc.) of the cooling zone and the plate passing speed. The specific residence time can be determined by the TTT curve obtained in the laboratory for different components in advance.
[0076] If the residence time between the solution temperature and 600°C is too short, too little Co-P compound will precipitate, and the precipitation strengthening effect of the present invention will not be achieved. If the residence time is too long, it is easy to cause the rapid growth of Co-P precipitates, and the effect of the present invention will also not be achieved. Within the composition range of the present invention, the effect can be achieved between 10-60 seconds. If the production equipment does not have the ability to monitor the temperature and adjust the cooling conditions, it can also be achieved by an intermediate heat treatment method (i.e., conventional solution-quenching treatment, then solution-quenching treatment at 600-700°C). It just increases the process and manufacturing costs.
[0077] 6. [Aging Processing]
[0078] Next, aging treatment is carried out. The aging treatment temperature is preferably between 350-500°C, and good results can be obtained when the aging treatment time is roughly in the range of 3-10 hours. The purpose of aging is to precipitate Mn-P compounds as much as possible and further precipitate Co-P compounds. The strength and conductivity of the material are improved by the superimposed precipitation effect of these two precipitates. Similarly, if the aging temperature is too low and the aging time is too short, the precipitation is insufficient; if the aging temperature is too high and the aging time is too long, it is easy to cause over-aging and low strength.
[0079] 7. [Final cold working]
[0080] In order to further improve the strength of the material, a final cold working with a rolling rate of 20-60% can be performed after aging treatment. As the processing rate increases, the strength increases, while the heat resistance and bending processability decrease. The inventors have found through detailed research and investigation that if the rolling rate is controlled between 20-60%, the strength, heat resistance and bending processability of the present invention can be achieved.
[0081] 8. [Low temperature annealing]
[0082] If the final cold working is carried out, low temperature annealing should be carried out after processing in order to reduce and eliminate the residual stress in the material and improve the heat resistance. At the same time, low temperature annealing can also improve the conductivity. The heating temperature in low temperature annealing can be set within 350-550℃, continuous annealing for a few seconds to a few minutes, or within 150-350℃, bell furnace annealing for a few hours. Correspondingly, if the temperature is set too high, it is easy to cause the softening of the plate. On the contrary, if the temperature is set too low, the expected effect cannot be achieved. 4. Embodiment
[0083] A square ingot with the composition shown in Table 1 was cast using a vertical semi-continuous casting machine. After the head and tail of the ingot were cut off, it was heated to 960 and kept for 3 hours before hot rolling. After hot rolling, it was water-cooled and the oxide film on the surface was removed by milling. It was then cold-rolled to the required thickness and then solution treated at 800-1000°C. For alloys with different compositions, metallographic observations at different solution treatment temperatures and times were observed in advance through laboratory experiments. The temperature and time corresponding to the average grain diameter of 8-15μm after solution treatment were used as the temperature of the heating and soaking zone of the continuous annealing furnace, and the time was obtained by the ratio of the furnace length of the heating and soaking zone to the plate passing speed.
[0084] The intermediate heat treatment is 600-700℃×1min, and the aging treatment is performed at 400℃. The hardness reaches the maximum value by adjusting the aging time at 400℃. The optimal aging treatment time for the alloy composition is known from previous experiments. The material sample after aging treatment is finally cold rolled with a rolling rate of 50%, and then low-temperature annealing is performed in a heating furnace at 400℃ for 1 minute. Pickling, degreasing, bending and straightening, and trimming are performed as necessary in the middle. Finally, the precipitates of the obtained plates are observed and the characteristics are evaluated. The plate thickness of the samples is uniformly 0.20mm. The main manufacturing conditions of each sample are shown in Table 2.
[0085]
Table 1
[0086]
[0087] Note: The underline indicates that it is beyond the scope specified in this invention.
[0088] The properties of the obtained samples were evaluated in terms of conductivity, tensile strength, heat resistance and bending properties.
[0089] [Electrical conductivity]: Measured according to the method specified in JIS-H0505.
[0090] [Tensile strength]: Measured according to the method specified in JIS-Z2241.
[0091] [Bending Processability]: Plate-shaped specimens (10 mm in width) cut in the length directions LD and TD were bent according to the 90° W-type bending method specified in JIS H3110. The surface and cross section of the specimen after bending were observed under an optical microscope at 100 times. The minimum bending radius R without cracking was obtained. The ratio R / t of the minimum bending radius R and the plate thickness t was used as an evaluation of the bending processability. The smaller the R / t value, the better the bending processability.
[0092] [Precipitate observation]: In order to reduce the influence of dislocation on precipitate observation, precipitate observation was carried out on the samples after aging treatment under (TEM observation conditions).
[0093] The results of the characteristic evaluation are shown in Table 2.
[0094]
Table 2
[0095]
[0096] Note: The underline indicates that it is beyond the specified scope of the present invention.
[0097] It can be seen from Table 2 that all the inventive examples have a good balance between conductivity and tensile strength under the composition requirements and manufacturing process conditions of the present invention, that is, the high-strength and high-conductivity factors (conductivity×tensile strength) are all greater than 450, and at the same time have good bending processability with R / t in both LD and TD directions being less than 2.0.
[0098] In contrast, Comparative Examples No. 11-14 are examples in which good properties are not obtained because the contents or ratios of Mn, Co and P exceed the range specified in the present invention. The contents of Mn, Co and P in No. 11 are too low, resulting in too few precipitates and low strength. Comparative Example No. 12 has too high contents of Mn, Co and P, especially the P content exceeds 0.40wt%, which causes hot rolling cracking and makes it impossible to carry out subsequent process and property evaluation. No. 13 and 14 are examples in which the (Mn+Co) / P ratio is too large and too small, that is, one of (Mn+Co) or P is relatively excessive, resulting in a small amount of precipitation, and relatively low strength and conductivity. No. 15 and 16 are examples in which the ratio of Mn to Co is too large and too small, resulting in low strength or conductivity. The Mn content in No. 15 is too small, resulting in a result similar to that of a general Cu-Co-P alloy, that is, high conductivity but low strength. On the contrary, the Co content of No. 16 is too low, resulting in a result similar to that of a general Cu-Mn-P alloy, that is, the tensile strength can reach a relatively high 747MPa, but the conductivity is only 55.1%IACS. No. 17 is an example of poor properties caused by excessive content of other elements. Since Ni can also form compounds with P, the excessive addition of Ni destroys the balance between Mn-Co-P, resulting in lower conductivity and tensile strength than the invention example.
[0099] Comparative Examples No. 21-23 are examples of alloys of Inventive Examples No. 1-3 with alloy composition, but the manufacturing process conditions are beyond the scope specified in the present invention, and good properties are not obtained. No. 21-23 did not undergo intermediate heat treatment, and the aging temperature and aging time were adjusted according to the usual process flow to achieve the optimal aging conditions. The other manufacturing conditions were the same as Inventive Examples No. 1-3, and the resulting strength and conductivity were much lower than Inventive Examples No. 1-3. No. 24 and No. 25 are examples of alloys of Inventive Example No. 2 with alloy composition, but the intermediate heat treatment conditions were not suitable, resulting in properties that did not achieve the effects of the present invention. The intermediate heat treatment temperature of No. 24 was too low and the time was too short, resulting in too few Co-P precipitates. The final conductivity and tensile strength were slightly higher than those of Comparative Example No. 22 without intermediate heat treatment, but far less than Inventive Example No. 2. No. 25 is an example of an intermediate heat treatment time that was too long or the temperature was too high, resulting in coarse Co-P precipitates and low strength.
[0100]
Observation of precipitates
[0101] The morphology of the precipitates in Comparative Examples No. 15 and No. 16 is close to the Cu-Co-P and Cu-Mn-P precipitates reported in various literatures, which are spherical and needle-shaped, respectively, and the results of high conductivity and low strength or the opposite are also consistent. Comparative Example 22 is the alloy composition invention example No. 2 of the present invention, a Cu-Mn-Co-P alloy in which Mn and Co are mixed in equal proportions, using conventional solid solution-quenching and no intermediate heat treatment process. As a result, needle-shaped and spherical precipitates are mixed, and the superposition strengthening effect of the two precipitates is not reflected. The obtained conductivity and strength are only in the middle position between Comparative Examples No. 15 and No. 16. The morphology of the precipitate in Inventive Example No. 2 is that the needle-shaped precipitates are contained (embedded) inside the spherical shape. Although the relationship between the two precipitates cannot be clearly defined at present, the result is that the needle-shaped precipitates are refined and the amount of precipitates is significantly increased, and the conductivity and strength are improved at the same time.
Claims
1. A copper alloy material, characterized in that: Containing 0.10-0.60wt% Mn, 0.15-0.50wt% Co, 0.04-0.39wt% P, and the remainder being Cu and inevitable impurities, the copper alloy material has a composition ratio relationship satisfying the following formulas (1) and (2): 0.25≤{Mn} / {Co}≤4.0……(1); 2.8≤({Mn}+{Co}) / {P}≤5.0......(2); Wherein {Mn}, {Co} and {P} represent the mass percentages of Mn, Co and P in the copper alloy material, respectively.
2. The copper alloy material according to claim 1, characterized in that: Containing 0.15-0.40wt% Mn, 0.15-0.35wt% Co, 0.06-0.23wt% P, and the remainder being Cu and inevitable impurities, the copper alloy material has a composition ratio relationship satisfying the following formulas (1) and (2): 0.5≤{Mn} / {Co}≤2.0……(1); 3.0<({Mn}+{Co}) / {P}<4.5......(2).
3. The copper alloy material according to claim 1 or 2, characterized in that: It also contains one or more selected from Ni, Fe, Mg, Cr, Sn, Zn, Zr, Ag, Ti and lanthanide rare earth elements, and the total amount is less than 0.2wt%.
4. The copper alloy material according to claim 1 or 2, characterized in that: It also contains one to three selected from Ni, Fe, Mg, Cr, Sn, Zn, Zr, Ag, Ti and lanthanide rare earth elements, and the total amount thereof is 0.075-0.15wt%.
5. The copper alloy material according to claim 1 or 2, characterized in that: The electrical conductivity and tensile strength satisfy the following formula (3): {EC}×{TS}≧450……(3); Wherein {EC} represents the electrical conductivity of the copper alloy material in %IACS, and {TS} represents the tensile strength of the copper alloy material in MPa.
6. The copper alloy material according to claim 1 or 2, characterized in that: The plate processed from the copper alloy material also has good bending processability with a minimum bending radius to plate thickness ratio R / t being less than 2.
0.
7. The method for producing the copper alloy material according to any one of claims 1 to 6, characterized in that: It includes the following steps performed in sequence: S1: Ingot cast by continuous or semi-continuous casting, hot processed by hot rolling, hot forging or hot extrusion; S2: Cold working by cold rolling, cold forging or cold drawing; S3: intermediate heat treatment at 600-700°C for 30 seconds to 3 minutes; S4: Aging treatment at 350-450℃ for 3-10 hours; S5: Low temperature annealing after cold rolling and final cold rolling.
8. The method for manufacturing a copper alloy plate material according to claim 7, characterized in that: The temperature of the hot working in S1 is 950-1000°C.
9. The method for manufacturing a copper alloy plate material according to claim 7, characterized in that: In the S3, an intermediate heat treatment is performed at 650-720° C. for 1 to 1.5 minutes; and in the S3, an aging treatment is performed at a temperature range of 380-420° C. for 3 to 6 hours.
10. The method for manufacturing a copper alloy plate material according to claim 7, characterized in that: The processing rate of the cold rolling is 20-60%.
Citation Information
Cited By
Cu-mn-co-p-based alloy and manufacturing method therefor
WO2026007951A1
Cu-fe-mn-p series alloy material and manufacturing method therefor
WO2026149299A1
